HIGHLIGHTING THE MAJOR HYDROLOGICAL EVENTS USING ²¹⁰PB RADIOMETRIC METHOD IN VALEA VINŢULUI RIVER - VASILACHE, Daniela; BICAN-BRIȘAN, Nicoleta; BEGY, Robert Csaba (Studia Universitatis Babeș-Bolyai Ambientum, 2015)
The growing interest in the dynamics of floodplains and the important role of alluvial sedimentation in river meadows, which acts as an archive of sediment, have focused on the need to document contemporary and recent sedimentation rates. This paper presents the results obtained of highlighting the major hydrological phenomena for Valea Vinţului and Pian river meadows, located in the Mureş river basin, characterized as high-risk flood areas. For the first time in Romania, ²¹⁰Pb radiometric method was used to obtain first estimates of sedimentation rate in a floodplain (Valea Vinţului river). After chemical preparation (acid leaching) of alpha spectrometric sources, ²¹⁰Pb concentrations in the samples were determined by measuring its daughter isotope ²¹⁰Po using the alpha spectrometer ORTEC Soloist, equipped with a PIPS detector with 900 mm2 active surface for recording of alpha particles 5,3 MeV ²¹⁰Po. Activities from 23±5 to 94±6 Bq/kg ²¹⁰Pb were found for Valea Vinţului river floodplain. After applying the CRS model (Constant Rate of ²¹⁰Pb Supply), the results of this method were compared with reports from literature and from the Water Management System Alba and there were observed periods of massive deposits due to floodings between years 1936 and 2012 (± 2 years) with a alluvial sedimentation rate of 1.863 ± 0.167 up to 6.185 ± 1 g/cm2*y.